Biometric and RFID based authentication system for exam paper leakages detection using IoT technology - J. Ann Roseela; T. Godhavari (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Education is the soul of a community; it goes from one generation to another. Exam is the prime responsibility of an educational framework. The reason for an examination is to select talented applicants for multiple positions. Exam is an important aspect of the education system to test students' abilities online and in oral papers. Every year we receive deferred/canceled exam messages due to paper leakage. Therefore, we have come up with a affordable and concise outcome, and we have decided to design and implement the "Exam Paper Leak Protection Framework", which will be a much more secure structure depending on the controller. Together with RFID Reader, Fingerprints sensor, Buzzer, LCD, and Wi-Fi module. First, the university will send a selection sheet to an educational institution "electronic sealed box" known the "electronic control box". Electronic control box is a prototype that can be proposed using controller, and the RTC to display the current date and time. If anybody tries to intrude the box the buzzer will beep and alert message will be send to the university.